The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1080/14767058.2016.1190827
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of personality profile and lactation differs between mothers of late preterm and term neonates

Abstract: Late preterm birth, a rapidly growing segment of premature deliveries, has the potential to cause deleterious effects on women's psycho-emotional experience of labor and the establishment of successful lactation. We compared personality traits by the Lüscher Color Test, the mother-to-infant bonding attitudes by the Mother-to-Infant Bonding Scale (MIBS) and lactation outcome, between mothers of late preterm and at term infants. Our results indicated that mothers idealize their condition and wish to enjoy this m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…Numerous authors [20,22,[27][28][29][30] have claimed that feeding difficulties impair the mother's mental health and the emotional bond between the mother-infant dyad, resulting in anxiety, stress, and depression. Maternal stress may be responsible for several hormonal changes, which may result in decreased milk supply and, on the other hand, impaired maternal behavior, a barrier to successful breastfeeding [27,28,33,34].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Numerous authors [20,22,[27][28][29][30] have claimed that feeding difficulties impair the mother's mental health and the emotional bond between the mother-infant dyad, resulting in anxiety, stress, and depression. Maternal stress may be responsible for several hormonal changes, which may result in decreased milk supply and, on the other hand, impaired maternal behavior, a barrier to successful breastfeeding [27,28,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Both the maternal psychological discomfort and the immature behavior of late preterm infants could hinder the interaction of the dyad, thus favoring a conflictual approach during feeding [28,[41][42][43]. Salvatori et al [42] showed that preterm dyads had fewer positive interactions during feeding times at 18 and 24 months than term dyads; moreover, preterm infants had increased food refusal behaviors from 18 months to 24 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations